Building in Post-war Environments. (2017) - Tortorici, Giovanni; Fiorito, Francesco
Abstract: Modern wars generate devastating effects on the environment by using chemical, biological, radioactive weapons. Toxic effects persist for long time on war fields. Negative environmental impacts such as desertification, migrant masses, depletion of natural resources (food, water, wood, etc.), and induced biodiversity produce, in turn, conflicts. This paper aims at i) identifying the consequences of conflicts and wars on the built environment with special reference to the industrial and residential buildings in urban areas; ii) determining the environmental impact of the procurement and use of natural resources and materials for the reconstruction of human settlements; iii) describing the results of this contribution according to their practical use. The research starts with a critical analysis of international examples related to modern wars. Contemporary situations of environmental degradation also related to major natural disasters that have altered the context in which they happened have been then analysed. Moreover, results of some significant interventions of environmental clean-up and building reconstruction have been examined, together with guidelines of the international humanitarian organizations on aspects of health and quality of life in areas with depleted environment. Results of these studies permit to suggest a post war methodology for the revitalization of the territory with restocking and monitored rebuilding, coordinated with contextual recovery of ecosystems. Construction techniques, with characteristics of resilience, habitability and sustainability are finally proposed. These solutions must also strive for reintegration of personal property and for the definitive localization of residents respecting their traditions and culture. Overall, this paper gives an operative contribution to one of the most important problems of humanity, which can be useful to future researches on territories marked by the environmental degradation caused by wars. Recovered environments, made sustainable, may help to understand that the real solution is avoiding wars and their deleterious effects.